Chronic kidney disease is a risk factor for cardiovascular disease - Swanepoel, CR (SA Heart Journal, 2017)
Chronic kidney disease (CKD) is common, harmful and treatable. There are no accurate statistics on the prevalence of kidney disease in South Africa but the world prevalence is estimated at approximately 10%. Patients with CKD have cardiovascular (CV) mortality rates as high as 50%. In addition to traditional risk factors, these patients are exposed to other non-traditional CV risk factors. It is important to stress that with the development of early CKD in the form of increasing albuminuria, even from within the normal range (a marker of endothelial dysfunction), the patient is at increased risk of coronary heart disease. “Reverse epidemiology” is the paradox where a high body mass index predicts a better long-term survival in patients with CKD on haemodialysis. Curiously these patients have increased inflammatory markers and atherosclerosis. “Confounding by disease” or “reverse causality” is used to explain why the traditional relationship of increased cholesterol, increased LDL cholesterol and CV risk is not present (except in nephrotics) in CKD. The high phosphate level predisposes to calcium phosphate crystal deposition in the vessels and heart valves. The resultant arteriosclerosis produces the increased pulse wave velocity and systolic hypertension. Rapid valvular calcification, aortic stenosis being a particular difficulty, and early onset coronary artery calcification occur. Arrhythmias are common and the long QT interval syndrome is particularly pertinent. The risk of acquired LQTS is increased by the administration of drugs. Cardiac troponin T is elevated in approximately 25% of asymptomatic patients with CKD. The use of angiotensin converting enzyme inhibitors and angiotensin receptor blockers have been shown to reduce proteinuria and to slow the progressive loss of renal function seen in CKD. These agents also improve cardiac outcomes and reduce the incidence of stroke. Most trials on the management of coronary artery disease have excluded patients with renal disease, and it remains unclear whether the results obtained from these trails can be extrapolated to patients with CKD.